2009
DOI: 10.1016/j.jmaa.2008.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Sums of Hilbert space frames

Abstract: We give simple necessary and sufficient conditions on Bessel sequences { f i } and {g i } and operators L 1 , L 2 on a Hilbert space H so that {L 1 f i + L 2 g i } is a frame for H. This allows us to construct a large number of new Hilbert space frames from existing frames.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 11 publications
2
24
1
Order By: Relevance
“…As can be seen in Definition 2.4, an oblique dual of a frame sequence is a natural symmetric dual of the frame sequence. Hence, this result on frame sequences contrasts with the result on the sum of a frame and one of its dual frame by Obeidat et al [19] mentioned previously.…”
Section: Sum Of a Frame Sequence And One Of Its Oblique Dualscontrasting
confidence: 98%
See 2 more Smart Citations
“…As can be seen in Definition 2.4, an oblique dual of a frame sequence is a natural symmetric dual of the frame sequence. Hence, this result on frame sequences contrasts with the result on the sum of a frame and one of its dual frame by Obeidat et al [19] mentioned previously.…”
Section: Sum Of a Frame Sequence And One Of Its Oblique Dualscontrasting
confidence: 98%
“…Possibly inspired by this result, Obeidat, Samarah, Casazza, and Tremain showed that, among other things, if F is a frame for and G is any one of its (alternate or generalized) dual frames (for ), then F + G is also a frame for [19]. This implies that F + G is a frame sequence if F is a frame sequence and G is a type I dual of F .…”
Section: Sum Of a Frame Sequence And One Of Its Type II Duals And Itsmentioning
confidence: 92%
See 1 more Smart Citation
“…Therefore L is invertible and so {f i } i∈I is a frame for H with the frame operator L −1 S L (L * ) −1 . Here, we also show that the equivalence of part (1) and (2) in Proposition 3.1 of [3], is not true in general. Indeed, if T 1 L * 1 + T 2 L * 2 is an invertible operator, then {L 1 f i + L 2 g i } i∈I is a frame for H but the inverse is not true.…”
Section: Proof Let Us Definementioning
confidence: 65%
“…There are many reference articles on such problems such as [11][12][13][14][15]. In [16], the authors studied the sums of Hilbert space frames, which is a simple way to construct a large number of new frames from existing frames, where just sums of two frames are considered. In this article, we will apply the techniques established in [4] to discuss the constructing problem.…”
Section: Introductionmentioning
confidence: 99%